The eICU Collaborative Research Database, a freely available multi-center database for critical care research - Pollard, Tom J.; Johnson, Alistair E. W.; Raffa, Jesse D.; Celi, Leo A.; Mark, Roger G.; Badawi, Omar (Scientific data, 2018)
Critical care patients are monitored closely through the course of their illness. As a result of this monitoring, large amounts of data are routinely collected for these patients. Philips Healthcare has developed a telehealth system, the eICU Program, which leverages these data to support management of critically ill patients. Here we describe the eICU Collaborative Research Database, a multi-center intensive care unit (ICU)database with high granularity data for over 200,000 admissions to ICUs monitored by eICU Programs across the United States. The database is deidentified, and includes vital sign measurements, care plan documentation, severity of illness measures, diagnosis information, treatment information, and more. Data are publicly available after registration, including completion of a training course in research with human subjects and signing of a data use agreement mandating responsible handling of the data and adhering to the principle of collaborative research. The freely available nature of the data will support a number of applications including the development of machine learning algorithms, decision support tools, and clinical research. Design Type(s) data integration objective • database creation objective Measurement Type(s) Administrative Activity • Clinical Evaluation • Care • Treatment Plan • Vital Signs Measurement Technology Type(s) documenting • performing a clinical assessment • multiparameter monitor Factor Type(s) anthropometric measurement • diagnosis • treatment Sample Characteristic(s) Homo sapiens • United States of America • hospital Machine-accessible metadata file describing the reported data (ISA-Tab format)